Validação ergonômica, situada e multiprofissional de brinquedo educativo: um estudo de caso do LOPU - Gonçalves , Shirley Belém (2015)
The objective of this research was to validate the educational toy LOPU as its contribution to the motor, social and intellectual development of children with typical and atypical development. For this validation, we used the ergonomic methodology to set and multi validation of educational toys (Saldanha, 2013, 2015) conducted by Participatory ergonomics (Hendrick, Kleiner, 2006; Saldanha, 2004), associated with the method of the Ergonomic Analysis of work- AET (Wisner, 1987; Guérin et al, 2001; Vidal, 2003), through a systematic process of social construction (Daniellou, 1988 Saldanha, 2004) and consists of the following steps: Education demand and social construction with institutions and participants; Adjustments in the design and construction of the toy prototype full-scale; Validation located and multi-use of educational toy for children with typical development and / or atypical, through designed plays, implemented and evaluated by specialized professionals; Tabulation and analysis of results for the toy contribution to the development of children's skills, the potential and limitations of the toy and improvement proposals for the toy design. Validation of LOPU occurred in basic education school in a federal university and a foundation to support people with disabilities. Validation was attended by 22 professionals (teachers, educators, speech therapists, psychologists, occupational therapists and rehabilitation), 60 children of typical development between the ages of 2 and 6 years, and 30 children and adolescents from atypical development (people with Down syndrome, intellectual disabilities , autistic, hearing impaired, visually impaired and cerebral palsy) aged 3 to 16 years. According to the school teachers, in 23 different games (25 applications) conducted with 60 children 2-6 years of typical development, LOPU contributed to the development of the following skills: Motor: locomotion (78%); gross motor coordination (48%) and fine (35%); balance (4%). Social interpretation (95%); response command (91%), communication (56%). Intellectual: visual perception (100%), and tactile (74%); association of ideas (95%); shape recognition (60%), numbers (48%), color (39%), letters (22%) animals (17%), senses and organs (9%), and transportation means (4%); Space concept and vocabulary (35%); counting (30%); writing (17%). In 23 games (32 applications) held with 30 children and adolescents with atypical development in Support Disabled Foundation, the professionals found that LOPU contributed to the development of the following skills: Motor: gross motor coordination (69%) and thin ( 39%); Locomotion (69%) and balance (48%). Social: Response command (74%), construction (69%) and communication (48%). Intellectuals: tactile and visual perception (95%), association of ideas (65%), space notion (53%), vocabulary (43%), count (26%), writing (4%), color recognition (48% ), numbers (30%), and forms fruit (22%); animals (17%) and transportation means (9%). The main positive features of the toy were playful aspect, arouse the attention and interest of children's learning, ease of interpretation and assembled by professionals, able to work various aspects of child development. The analysis of the weaknesses, difficulties, limitations and suggestions for improvements, possible adjustments in the final design of LOPU.